Decision making in capital budgeting : a case study of a newly-established sugar plant in Pakistan - Sadiq, Earnest; Gupta, Joyti; Jain, P. K.; Igel, Barbara (Bangkok : Asian Institute of Technology, 1997)
The investment decisions are the most important decisions in the business, because these decisions determine the future size, profitability, and goodwill of the company. Moreover, investments need sacrifice of the resources available to a firm. The irreversibility of the investment decisions also depicts the importance of the decision. As complexity and dynamism of the business world is enhancing day by day, the investment decisions are becoming more and more difficult. This research stud)' is an attempt to provide an insight into the investment decision made in a sugar industry in Pakistan. For this purpose, a newly established sugar plant is selected and then decision making process is scrutinized from initial stages to final stages. The data are collected from secondary sources like company books, brochures and annual report as well as primary sources like managers. Further these data are analyzed and discussed. Investment in sugar plant is involves quite a big amount. To check the viability of the investment, different aspects of sugar industry are discussed and compared with the other countries of the world. It is found that sugar industry of Pakistan is under performing when compared with other countries of the world. Regarding financial aspect of decision, some flaws are found in decision making process. Some of the practices followed by the company do not comply with literature. Modem techniques like , discounted cashflows, are not used to evaluate the investment proposal.
A research study submitted in partial fulfillment of the requirement for the degree of Master of Business Administration.
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1997
Keywords: Capital budget -- Pakistan; Capital budget -- Decision making